Sure...
first we want to combine like terms on each side of the equals sign. Think of the equals like the balance point on a scale... you can do anything on one side as long as you match it (keep it balanced) on the other!
so we want to combine the variables and the constants...
8a - 3a + 4 = -a -4 + 2
5a + 4 = -a - 2
now we want all the variables on one side, and constants on the other:
5a -(-a) + 4 - 4 = -a-(-a) - 2 - 4
5a + a = -2 - 4
6a = -6
now we just divide by 6 to get a alone:
6a/6 = -6/6
a = -1
Hope this helps! :)
2006-11-08 10:27:53
·
answer #1
·
answered by disposable_hero_too 6
·
0⤊
0⤋
You sure u not looking for someone to do your homework? lol anyway:
8a + 4 - 3a = -4-a + 2
(8a -3a) + 4 =(- 4 + 2 )- a Bring like together
5a + 4 = - 2 - a
5a + a = - 4 -2
6a = -6
Therefore a = -6/6
a = -1
Hope you understand. To make sure substitute -1 for "a" in the original question and you will see that it works out.
2006-11-08 18:38:30
·
answer #2
·
answered by hotredrasta 1
·
0⤊
0⤋
8a + 4 -3a = -4-a+2
all the a's need to be on one side and all the numbers on the other
8a -3a +a = -4 +2 -4
6a = -6
Divide both sides by 6
6a/6 = -6/6
a= -1
2006-11-08 18:32:49
·
answer #3
·
answered by shootingstar0212 3
·
0⤊
0⤋
a= -1
2006-11-08 18:30:17
·
answer #4
·
answered by crawlingman 2
·
0⤊
0⤋
8a + 4 -3a = -4 -a + 2
8a -3a + 4 = -a + 2 -4
5a + 4 = -a - 2
5a + a = -2 -4
6a = -6
a = -6/6
a = -1
2006-11-08 18:48:48
·
answer #5
·
answered by Dr. J. 6
·
0⤊
0⤋
8a + 4 - 3a = -4 - a + 2
5a + 4 = -2 - a
6a = -6
a = -1
2006-11-08 18:28:12
·
answer #6
·
answered by Harry B 2
·
0⤊
0⤋
First, isolate the variable, so it is only on one side of the problem:
8a+4-3a+a=-4+2
8a-3a+a+4=-4+2
6a+4=-4+2
6a+4=-2
6a=-2-4
6a=-6
6a/6=-6/6
a=-1
2006-11-08 18:41:45
·
answer #7
·
answered by Richard H 7
·
0⤊
0⤋
8a+4-3a = -4-a+2
8a-3a+a = -4+2-4
6a = -6
a = -1
2006-11-08 18:33:48
·
answer #8
·
answered by Al G Bra 1
·
0⤊
0⤋
8a+4-3a=-4-a+2
5a+4=-2-a
6a=-6
a= -1
2006-11-08 18:28:41
·
answer #9
·
answered by jamie23 3
·
0⤊
0⤋
I think its 11a+4=-2-a
8a+4-3a=-4-a+3
make it all addition
8a+4+(-3a)=-4+(-1a)+3
combine like terms
8a+(-3a) and -4+3
5a+4=-1a+-1 - thats your answer.
2006-11-08 18:32:11
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋